How can management ability promote green technology innovation of manufacturing enterprises? Evidence from China - Guang-lin, Xu; Tao, Meng (Frontiers in Environmental Science, 2023)
Management ability improves organizational learning and innovation ability, thereby improving enterprise performance. Higher-ability management has more flexible and adaptive strategic thinking and ability, allowing it to quickly capture market opportunities, formulate long-term digital transformation strategies, gain competitive advantage through product and service innovation, and thus promote enterprise innovation performance. The research sample for this paper is A-share listed companies in the manufacturing industry from 2008 to 2019, and it integrates management capabilities with digital economy and green technology innovation. Our research shows that management ability can significantly boost manufacturing enterprises’ green technology innovation. Furthermore, regardless of whether the enterprise is state-owned or non-state-owned, management ability is positively related to green technology innovation performance, and internal control has a significant positive regulating effect on the relationship between them. Given these findings, this study offers important insights for strengthening the integration of the digital economy and green transformation, emphasizing the rationality of management capabilities, and developing policies for various enterprises.